2008
DOI: 10.1124/jpet.107.131060
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Role of Mitogen-Activated Protein Kinase Signaling Pathways in the Development of Spinal Cord Injury

Abstract: Mitogen-activated protein kinase (MAPK) signaling pathways involve two closely related MAPKs, known as extracellular signal-regulated kinase (ERK)1 and ERK2. The aim of the present study was to evaluate the contribution of MAPK3/MAPK1 in the secondary damage in experimental spinal cord injury (SCI) in mice. To this purpose, we used 2-(2-amino-3-methoxyphenyl)-4H-1-benzopyran-4-one (PD98059), which is an inhibitor of MAPK3/MAPK1. Spinal cord trauma was induced by the application of vascular clips (force of 24 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…The two damage mechanisms of primary and secondary SCI may combine to seriously affect human health and quality of life; potentially causing disabling injuries (14). Primary SCI occurs instantly after injury of spinal cord tissue due to exposure to external forces, and is an irreversible form of damage (17). On the basis of primary injury in the spinal cord tissue, the progressive, self-destructive cascade amplification destruction process caused by a variety of factors is known as secondary SCI; the degree of damage is substantially more than in primary SCI (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two damage mechanisms of primary and secondary SCI may combine to seriously affect human health and quality of life; potentially causing disabling injuries (14). Primary SCI occurs instantly after injury of spinal cord tissue due to exposure to external forces, and is an irreversible form of damage (17). On the basis of primary injury in the spinal cord tissue, the progressive, self-destructive cascade amplification destruction process caused by a variety of factors is known as secondary SCI; the degree of damage is substantially more than in primary SCI (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Primary SCI occurs instantly after injury of spinal cord tissue due to exposure to external forces, and is an irreversible form of damage (17). On the basis of primary injury in the spinal cord tissue, the progressive, self-destructive cascade amplification destruction process caused by a variety of factors is known as secondary SCI; the degree of damage is substantially more than in primary SCI (17)(18)(19). The present study further showed that BBB scores and contused volume in rats post-SCI were improved and suppressed by treatment with tocotrienol, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…bolus) 1h aftercarrageenan administration of saline (N=10). The doses of PD98059 (10 mg kg') used here were based on previous in vivo studies that demonstrated a regulation of inflammation process (13)(14).…”
Section: Experimental Designmentioning
confidence: 99%
“…It has been reported that ERK1/2 is activated in models of reperfusion and excitotoxic SCI, 31,32 and ERK activation is involved in post-SCI neuronal survival. 33,34 Fibulin-1 was previously established as a modulator of FN-stimulated ERK signaling, and it suppresses FN-regulated cell adhesion and motility. Furthermore, research by Selwyn et al showed that fibulin-1 can alter ECM-mediated cell signaling through inhibiting ERK activation.…”
Section: Discussionmentioning
confidence: 99%